Early Radiographic Outcomes of Vascularized Pedicle Bone Grafting in Foot: A Case Series - Coxe, Francesca R.; Bogner, Eric A.; Cooke, Margaret E.; O'Malley, Martin J.; Ellis, Scott J.; Fufa, Duretti T. (Journal of Reconstructive Microsurgery Open, 2022)
Background Navicular nonunion and talar avascular necrosis may result from limited blood supply predisposing to injury and impaired healing. Vascularized pedicled bone grafting is a promising adjunct to treat these challenging conditions, offering the susceptible diseased site structural and vascular support. We report the early radiographic and clinical outcomes of vascularized pedicled bone grafting in patients with navicular nonunion, talonavicular fusion nonunion, and talar avascular necrosis.Methods Patients with navicular nonunion, talonavicular fusion nonunion, or talar avascular necrosis who underwent vascularized pedicled bone grafting at our institution from January 2014 to February 2019 were retrospectively identified. Radiographic evidence of healing was monitored postoperatively as defined by: progression toward union on CT for nonunion and absence of disease progression on MRI or CT for avascular necrosis. Surgical complications and need for additional surgeries were documented.Results Eight patients were included who underwent vascularized pedicled bone grafting for navicular nonunion (N = 5), talonavicular fusion nonunion (N = 1), and talar avascular necrosis (N = 2). Average clinical follow-up was 10.8 months (range 4–37). All patients had 4 or more months postoperative radiographic follow-up with MRI or CT. Seven of eight patients demonstrated evidence of radiographic healing. One patient required additional surgery due to external fixator pin site infection. No other complications were reported.Conclusion Our results corroborate prior case series suggesting vascularized pedicled bone grafting is a safe and reliable procedure for treating navicular nonunion, talonavicular fusion nonunion, or talar avascular necrosis with potential to spare or delay need for salvage procedures in the younger patient population.Level of Evidence The evidence level is Level V.
Keywords: navicular; nonunion; talus; necrosis; pedicle; graft